2019
DOI: 10.1088/1367-2630/ab4fc4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-agent paradoxes beyond quantum theory

Abstract: Which theories lead to a contradiction between simple reasoning principles and modelling observers' memories as physical systems? Frauchiger and Renner have shown that this is the case for quantum theory (Frauchiger and Renner 2018 Nat. Commun. 9 3711). Here we generalize the conditions of the Frauchiger-Renner result so that they can be applied to arbitrary physical theories, and in particular to those expressed as generalized probabilistic theories (GPTs) (Hardy 2001 arXiv:quant-ph/0101012; Barrett 2007 Phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…One may also ask whether the conclusions obtained from the thought experiments presented here are specific to quantum theory, or whether they hold more generally. In [79], it was shown that, within the framework of generalised probability theories [80][81][82], which generalise the operational aspect of quantum theory, this is indeed the case for an experiment analogous to the FR thought experiment. Conversely, one may also apply classical multi-agent modal logic [83] to investigate Wigner's friend type experiments.…”
Section: Gödel's Theorem and Further Thought Experimentsmentioning
confidence: 99%
“…One may also ask whether the conclusions obtained from the thought experiments presented here are specific to quantum theory, or whether they hold more generally. In [79], it was shown that, within the framework of generalised probability theories [80][81][82], which generalise the operational aspect of quantum theory, this is indeed the case for an experiment analogous to the FR thought experiment. Conversely, one may also apply classical multi-agent modal logic [83] to investigate Wigner's friend type experiments.…”
Section: Gödel's Theorem and Further Thought Experimentsmentioning
confidence: 99%
“…One of the latest development in this way is quantum modal logics. The research have been done by A. Baltag and S. Smets [4,5], F. Boge [8], V. Vilasini [22] and N. Nurgalieva [17]. Our study covers field of logic of correlated knowledge which is part of quantum modal logics.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting works such as one relating the FR Gedankenexperiment to Generalized Probability Theories (GPT) can be found in Vilasini, Nurgalieva and del Rio. 32 A disclaimer between the usually mistaken concepts of formalism and interpretation is made on Baumann and Wolf. 33 Philosphical digressions on the proper language used within the literature about this problem and an analysis of how much this problem could properly contribute to the evolution on the state-of-art of the measurement problem are shown in Hansen and Wolf.…”
Section: "What Would Happen In a Wigner's Friend Scenario If Internalmentioning
confidence: 99%
“…Let us now transform the elements of the basis which constitutes f ij (t). Begining with f ij (t) = 1, 32) and with a simple change of variable u =…”
Section: Symmetrizationmentioning
confidence: 99%
See 1 more Smart Citation